Transcriptional memory of gene expression across generations participates in transgenerational plasticity of field pennycress in response to cadmium stress - Li, Gengyun; Zhao, Yuewan; Liu, Fei; Shi, Minnuo; Guan, Yabin; Zhang, Ticao; Zhao, Fangqing; Qiao, Qin; Geng, Yupeng (Frontiers in Plant Science, 2022)
Transgenerational plasticity (TGP) occurs when maternal environments influence the expression of traits in offspring, and in some cases may increase fitness of offspring and have evolutionary significance. However, little is known about the extent of maternal environment influence on gene expression of offspring, and its relationship with trait variations across generations. In this study, we examined TGP in the traits and gene expression of field pennycress (Thlaspi arvense) in response to cadmium (Cd) stress. In the first generation, along with the increase of soil Cd concentration, the total biomass, individual height, and number of seeds significantly decreased, whereas time to flowering, superoxide dismutase (SOD) activity, and content of reduced glutathione significantly increased. Among these traits, only SOD activity showed a significant effect of TGP; the offspring of Cd-treated individuals maintained high SOD activity in the absence of Cd stress. According to the results of RNA sequencing and bioinformatic analysis, 10028 transcripts were identified as Cd-responsive genes. Among them, only 401 were identified as transcriptional memory genes (TMGs) that maintained the same expression pattern under normal conditions in the second generation as in Cd-treated parents in the first generation. These genes mainly participated in Cd tolerance-related processes such as response to oxidative stress, cell wall biogenesis, and the abscisic acid signaling pathways. The results of weighted correlation network analysis showed that modules correlated with SOD activity recruited more TMGs than modules correlated with other traits. The SOD-coding gene CSD2 was found in one of the modules correlated with SOD activity. Furthermore, several TMGs co-expressed with CSD2 were hub genes that were highly connected to other nodes and critical to the network’s topology; therefore, recruitment of TMGs in offspring was potentially related to TGP. These findings indicated that, across generations, transcriptional memory of gene expression played an important role in TGP. Moreover, these results provided new insights into the trait evolution processes mediated by phenotypic plasticity.